Early return to work: Single-port vs. multiport laparoscopic surgery for benign ovarian tumor - Tang, Ying; Wen, Ming-bo; Su, Bin; Wang, Hang; Zheng, Xue-mei; Yang, Ming-tao; Yin, Shu; Xu, Fan; Hu, Hui-quan (Frontiers in Surgery, 2022)
Objective: To compare the return to work (RTW) time between single-port laparoscopic surgery (SPLS) and multiport laparoscopic surgery (MPLS) for benign ovarian tumors. Methods: A cross-sectional cohort study was conducted, consisting of 335 women with benign ovarian tumors at reproductive age and urgent to return to work. Surgical outcomes, postoperative pain score, postoperative satisfaction with cosmesis score (CS), RTW time of the SPLS group were compared with those of the MPLS group. Besides, RTW time and CS were calculated from the questionnaire survey by a single specialized gynecologist. Results: Women meeting the inclusion criteria were included into the SPLS group (n=106) and the MPLS group (n=229). The RTW time in the SPLS group (37.3±30.4 days) was significantly shorter than that in the MPLS group (64.4±59.8 days) (P＜0.001). The multivariate Cox analysis results showed that age (HR=0.984, 95%CI: 0.971-0.997, P=0.020), SPLS (HR=3.491, 95%CI: 2.422-5.032, <0.001) and return to normal activity time (HR=0.980, 95%CI: 0.961-0.998, P=0.029) were independent factors of the RTW time. Conclusions: SPLS may be advantageous to shorten the RTW time for benign ovarian tumors.